Vibration control of two-mass rotary system using improved NCTF controller for positioning systems - Mohd. Yakub, Mohd. Fitri; Martono, Wahyudi; Akmeliawati, Rini (2010)
In this paper, a nominal characteristic trajectory following (NCTF) controller for point-to-point (PTP) positioning system for two mass rotary system is introduced and its performance is evaluated. Generally, the NCTF controller consists of a nominal characteristic trajectory (NCT) and a compensator. The objective of the NCTF controller is to make the object motion follow the NCT and end at its origin. The NCTF controller is designed based on a simple open-loop experiment of the object. The parameters and an exact model of the plant are not necessary for controller design. This paper presents a method to improve the existing NCTF controller for two mass rotary positioning system by adding a notch filter as a compensator to eliminate the vibration due to the mechanical resonance. They can often remove resonance without compromising performance. The improved NCTF controller is evaluated and discussed based on results of simulation. The effect of the design parameters on the robustness of the NCTF controller to inertia and friction variations is evaluated and compared with conventional PID controller. It is shown that improved NCTF controller is better than conventional PID controller.